GEOGRAPHY OF THE MIGRATION OF THE POPULATION OF UKRAINE TO THE COUNTRIES OF EUROPE: ANALYSIS OF THE POLICY OF INTEGRATION OF MIGRANTS IN THE COUNTRIES OF DESTINATION - Alisa S. Mahdich (Akademičnij Oglâd, 2022)
This study is devoted to the analysis of the geography of migration of the population of Ukraine over the last decade on the basis of the Global Index of Migrant Integration Policy (MIPEX) and the identification of factors that attract the population of Ukraine to migrate to other countries. According to European Commission statistics since 2014, the number of Ukrainian labor migrants moving to the European Union (EU) has increased significantly. In 2019, Ukrainian citizens received 660,000 residence permits for paid activities in member states – the largest external labor force in the EU. Thus, the dependence of Member States’ economies on Ukrainian workers has reached significant levels, as evidenced by the labor shortages observed during the COVID-19 crisis, which forced the EU to close its borders. Emigration reduces the supply of labor and accelerates the growth of wages of workers who remain in the country; one of the problems of concern is the loss of skills – most of Ukrainians work abroad without qualifications or do very simple work. The main benefit for the Ukrainian economy is related to the remittances, equivalent to 8% of GDP. Remittances significantly improve the well-being of migrant families and stimulate domestic demand, increasing the country’s GDP. Stable and significant inflow of remittances contributes to a more stable balance of payments, compensation for the constant deficit of trade and investment income. At the same time, there is a risk that migrants will remain permanently resident abroad, which will mean a decrease in the working population in Ukraine. In addition, the impact of emigration and remittances on Ukraine’s public finances is ambiguous: remittances increase VAT, excise and customs revenues, while reducing labor supply reduces revenues from labor taxes and social security contributions in Ukraine. Therefore, it is important to understand what factors currently attract the population of Ukraine to other countries. The Migrant Integration Policy Index (MIPEX) is an index that measures the quality of migrant integration policy in 52 countries. The index indicators were developed for a multidimensional view of migrants’ opportunities to participate in public life. The index is a tool for evaluating and comparing the actions of governments to promote the integration of migrants in all analyzed countries. The index helps to understand and analyze the factors that contribute to the integration of migrants. The index covers the following areas of integration: labor market mobility; family reunification; access to services in the field of education; participation in political life; obtaining permanent residence; obtaining citizenship; antidiscrimination; access to health services.